The Efect of Market Timing on Capital Structure in Non-Financial Companies Conducting Intial Public Offering (IP0s) The Indonesian Stock Exchange in 2020-2021 - Mar’Atun Sholeha; Ernie Hendrawaty (International Forum of Researchers and Lecturers, 2025)
Capital structure is a strategic decision made by companies in determining the combination of debt and equity financing. Financial market dynamics can influence companies' strategies for obtaining financing for expansion, operations, or financial restructuring. Companies have the flexibility to determine when and how to obtain financing by considering market conditions, a practice known as market timing. This study aims to examine the impact of market timing on capital structure and to determine the persistent long-term effects of market timing. The research focuses on non-financial companies that conducted an initial public offering (IPO) in 2020-2021, with a population of 105 companies. A purposive sampling technique was employed, using specific criteria, resulting in a sample of 65 companies. The data used are secondary data analyzed using multiple linear regression with panel data. The results indicate that market timing, measured by the market-to-book ratio, has a significant negative impact on capital structure. The study also shows that market timing, does not have a persistent impact on capital structure in the long term. Companies tend to take advantage of momentum when stock valuations are high by conducting initial public offerings, while in the long term, companies tend to make adjustments, so the impact of market timing does not last long.